2001
DOI: 10.1021/ol016673j
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Reagent Control of Diastereoselectivity in the 1,2-Addition of Hard Carbon Nucleophiles to C6-Heteroatom Substituted Cyclohexenones

Abstract: [reaction: see text] A surprising and synthetically useful counterion-dependent reversal of diastereoselectivity was found in 1,2-additions of hard carbon nucleophiles to C(6)-heterosubstituted cyclohexenones. In general, Grignard reagents added syn to the C(6)-substituent and Li reagents added anti, although some exceptions were found. Selectivities could be increased in some cases by appropriate choice of solvent and/or cosolvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Even though the abovementioned differences bare intrinsic informational value, the exact identity of the diastereoisomers was not uncovered in neither case and, therefore, unambiguous conclusions regarding stereocontrol cannot be drawn. It is important to note that the exact nature of the metal acetylide, as well as other factors contributing to π-face selection render the reasons for these differences far from obvious. , High yields and remarkably high diastereoselectivities were obtained when norbornanone was used in combination with pyrrolidine and piperidine, leading to single diastereoisomers of tetrasubstituted propargylamines 4g and 4h , respectively. Benzylamine was also successfully coupled with norbornanone and phenylacetylene, albeit leading to a substantially lower yield of propargylamine 4k , a fact which is attributed to the increased stability of the intermediate imine.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the abovementioned differences bare intrinsic informational value, the exact identity of the diastereoisomers was not uncovered in neither case and, therefore, unambiguous conclusions regarding stereocontrol cannot be drawn. It is important to note that the exact nature of the metal acetylide, as well as other factors contributing to π-face selection render the reasons for these differences far from obvious. , High yields and remarkably high diastereoselectivities were obtained when norbornanone was used in combination with pyrrolidine and piperidine, leading to single diastereoisomers of tetrasubstituted propargylamines 4g and 4h , respectively. Benzylamine was also successfully coupled with norbornanone and phenylacetylene, albeit leading to a substantially lower yield of propargylamine 4k , a fact which is attributed to the increased stability of the intermediate imine.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of ester 2 (available in three steps from ( S )-(+)-carvone) with KHMDS and TIPSOTf afforded a single stereoisomeric product 3 possessing the Z -alkene and the ( S )-stereochemistry at C7 (Scheme ). The Ireland−Claisen rearrangement presumably proceeded via a chairlike transition state analogous to conformer i , with the larger C11 substituent occupying the pseudoequatorial position.…”
mentioning
confidence: 99%
“…29 We envisioned 1,2-addition of a two-carbon nucleophile to the ketone within 7 to construct the tertiary alcohol of the target. However, consistent with the studies by McIntosh and co-workers, 41 signicant optimization was required to obtain the cis-1,2-addition product in high yield and stereoselectivity. Aer much empirical experimentation, we found that the addition of ethylmagnesium bromide to solutions of the ketone 7 in toluene at À78 C provided the tertiary alcohol 11 in 70% yield and with 4 : 1 diastereoselectivity in favor of the desired product 11.…”
Section: Resultsmentioning
confidence: 54%